Strategi Meningkatkan Pemerolehan Bahasa Arab dengan Memperhatikan Tipe Kepribadian Siswa - Tsaniananda Fidyatul Chafidzoh (Al-Ma‘rifah, 2020)
The Arabic language is often categorized as a second language that is hard to learn and practiced as a means of communication. Although the government has made the Arabic language as the subject of elementary school through college, it does not make the Arabic language acquisition is easier and practicable for students to learn it. The level of language acquisition of each person is different; some can easily absorb the new language. This is because language acquisition is based on a natural process beneath the conscious. Therefore, by using descriptive qualitative research methods, this study aims to find the appropriate strategies for improving Arabic language acquisition based on student personality. The result of this study proves that extrovert or introvert personalities have different approaches to language acquisition. Extroverts tend to be more open, while introverts tend to be more closed. Extrovert personalities with more open tendencies have a more spontaneous language acquisition pattern, whereas introvert personalities with more inclined tendencies have a more disciplined and structured language acquisition pattern.